Development of Interactive Multimedia in Class V Elementary School Science and Science Subjects - Putra, Pelka Andesa; Zen, Zelhendri; Hendri, Nofri; Pratiwi, Rahmi (Lembaga Penelitian dan Pendidikan Mandala, 2025)
The development of technology brings changes in the use of learning media. One of the learning media that responds to technological developments is interactive multimedia. This study aims to produce interactive multimedia that is suitable for use as a learning media in the subject of Science for Grade V Elementary School. This study is a research and development study, with the selected development design using the ADDIE model (analyze, design, development, implementation, evaluation). The media that has been developed is evaluated by material experts and media experts to determine its feasibility. Based on the findings, media experts have an average feasibility value of 4.96 (very valid) by validator I, and an average of 4.68 (very valid) by validator II, while material experts have an average feasibility value of 4.74 (very valid). In addition, the results of the student response questionnaire after the trial of using interactive multimedia showed an average value of 4.81 (very practical), and the results of the effectiveness test of the post-test scores of students consisting of 20 students with the N-gain formula obtained a value of 0.73 (high). Thus, the development of interactive multimedia in the fifth grade science subjects isdeclared very valid and can be used without the need for improvement.